Effect of Magnetic Flux on the Quantum Transport in a Biphenyl Molecule - Dudeja, Suman; Bhattacherjee, Aranya B.; Gevorgyan, Narine (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2014)
We report influence of magnetic flux on the quantum transport in a aromatic π conjugate system made up of two phenyl rings separated by an insulator group. In the presence of a transverse magnetic field the transmission, the dipole moment and the energy of the system gives oscillatory behaviour with flux φ, threaded by the molecular ring showing flux quantum periodicity. This aspect may be utilized in designing nano-scale electronic devices.